Enhancing electrocatalytic hydrogen evolution by nickel salicylaldimine complexes with alkali metal cations in aqueous media - Shao, Haiyan (2018)
New salicylaldimine nickel complexes, comprising only earth-abundant elements, have been developed for electrocatalytic hydrogen evolution in aqueous media. The second-sphere ether functionalities on the periphery of the complexes enhance the electrocatalytic activity in the presence of alkali metal cations. The electrocatalysts demonstrate improved performances especially in the economical and sustainable seawater reaction medium.